ANALISIS PENGARUH STRUKTUR AKTIVA DAN RETURN ON EQUITY (ROE) TERHADAP STRUKTUR MODAL DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2012-2016 - Siti Reuni Inayati (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2019)
This study aims to examine and analyze how the influence of the Asset Structure, Return On Equity (ROE) and Firm Size as a moderating variable on the Capital Structure. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange. The sample of companies used were 17 companies with the study period from 2012 to 2016 with the Purposive Sampling method as sample selection. The test results show that the Asset Structure variable has no effect on the Capital Structure and Return On Equity (ROE) has a significant positive effect on the Capital Structure. While the interaction of Asset Structure with Company Size as a moderating variable does not affect the Capital Structure and the interaction of Return On Equity (ROE) with Firm Size as a moderating variable has no effect on the Capital Structure.